Representational and Ideational Meaning in Constructing Meaning in the Video Wonderland Indonesia: The Sacred Nusantara - Rokhman, Nabilah Farisah (Language Horizon: Journal of Language Studies, 2023)
Indonesia is a country that has a wealth of natural resources and cultural diversities. So, the researcher examined this research using object from the video Wonderland Indonesia: The Sacred Nusantara. This video contains the diversities and wonders of the Nusantara, which describes the natural beauty of Indonesia. This research aims to find out the representational and ideational meanings using multimodality discourses analysis. These show the audience through three aspects: process, participants, and circumstances. And the researcher find out the interplay of visual and linguistic modes to convey the meaning. In this study, the researcher analyzed visual images and linguistic text perspective supported by Kress van Leeuwen’s reading visual grammar theory and Halliday’s Systemic Functional Linguistics approach. The two modes of visual and linguistic complement each other in constructing representational meaning and ideational meaning.